STRATEGIES FOR VALUE ENHANCEMENT OF THE ARCHAEOLOGICAL SITE “CANTAMARCA” DEVELOPMENT OF SUSTAINABLE TOURISM IN THE PROVINCE CANTA - Cruz Gonzales, Niko (2014)
Research by team members: “Tourism towards the Bicentennial” Cantamarca Archaeological Site (located in the province of Canta) developing a situational analysis in order to raise the processes and strategies to develop the enhancement of the archaeological site. Cantamarca comes from two words, the first “Canta” was the name of the people who inhabited this place, and “marca”, which means “people” or “place” turn the first word “Canta” is attributed the great hunters of vicuña, so the final name becomes complex in the translation of “People of great hunters vicuna.” According to historian Dr. Maria Tovar Rostworowski and Arqul. Carlos Arturo Farfán Lobatón mention that Cantamarca was built during the Late Intermediate Period (1100 AD) and survived the conquest of the Incas (1450), who the reorganized and expanded until 1550 when the new Spanish conquistadors relocated its residents in the present town of Canta, and finally abandoned Cantamarca. From your brief reconnaissance describes its architecture, particularly the following groups: A) The wall ring, B) The aqueduct, C) or the Inca constructions “Tampus” the “Pucara” or Atalaya E), D) The pre-Inca constructions F) military town homes and graves; G ) strong containment, H) burial caves. The archaeological site of Cantamarca, was declared Cultural Patrimony of the Nation by National Directorial Resolution No. 2006 051/INC for conservation, preservation and promotion as a top tourist destination of the province. The importance of this research project is the first effort at the level of the province of Canta regain a cultural heritage, prioritized and developed through joint actions, so in order to give people new options for sustainable development, both tourism, social, cultural and economic level.